Songs My Mother Sang to Me : An Oral History of Mexican American Women - Martin, Patricia Preciado (Book collections on Project MUSE., 1992)
In ten oral histories recorded by Martin, Mexican American women of the Southwest reach as far back as the turn of the century to recall family history and genealogy, secular and religious traditions, work and leisure, living conditions, and personal values.